The usage of Microsoft Onedrive among the professional college staff/ Saiful Redzuan Mohamad and Norhayati Hussin - Mohamad, Saiful Redzuan; Hussin, Norhayati (Faculty of Information Management, 2021)
This research paper is written to provide a hypothetical study on the Unified Theory of Acceptance and Use of Technology (UTAUT) model by Venkatesh et al. (2003); framework on Microsoft OneDrive usage acceptance in one of the established professional college in Malaysia. Questionnaires were distributed to 130 staff and lecturers at one of the branches with 107 returned, an 82.3% return rate. Statistical Package for the Social Sciences (SPSS) version 22 has been used to analyse the data collected. Five variables involved in this study which are Performance Expectancy, Effort Expectancy, Social Norm, Facilitating Conditions and Usage Acceptance. The study recommends future studies should include a bigger scale of the sample that consists of all the professional college branches and add more variables such as trust and security.